KETEPATAN PEMBERIAN ANTIBIOTIK PADA PASIEN ISPA BAGIAN ATAS DI PUSKESMAS PEKAN LABUHAN MEDAN PADA BULAN JANUARI – JUNI 2017 - Eva Sartika Daposang; Atin Juniati (Universitas Medan Area, 2018)
Acute respiratory tract infection is one of the diseases that attack the main chanel of the raspiration of the nose, alveoli, andeksana, sinus, middle ear cavity and pleura. Acute infection is an infection that lasts for a 14 day time limit. This study aims to determine the accuracy of antibiotics in patients with URI in public health center Pekan Labuhan Medan is in accordance or not in accordance with the basic treatment guidelines in public health center 2007. Administration of antibiotics based on diagnosis of upper respiratory infection patients at Public Health Center Pekan Labuhan Medan of 93,2% there is not yet according to basic treatment guidance in Public Health Center 2007 which is set. Such discrepancies include the type of antibiotics and the suitability of the indication of administration.